HISTOPATHOLOGICAL CHANGES IN EXPERIMENTALY INFECTED MICE WITH PCR IDENTIFIED Corynembacterium psuedotuberculosis (Journal of Veterinary Medicine and Animal Production, 2022)
This study was done to investigate the histopathological responses of the early phase during experimental Corynebacterium pseudotuberculosis infection in white mice. Corynebacterium pseudotuberculosis strains were isolated from natural cases of caseous lymphadenitis (CLA) in sheep. The experimental infection was done by using five isolates. These isolates were confirmed by PCR and they showed different biochemical characters. The experiment comprised five groups of five mice each; inoculated subcutaneously with C. pseudotuberculosis strains and observed for ten days following inoculation. There were different pathogical involvement of the isolates, these included; focal infiltration of polymorphoneuclear cells was seen in liver, lung, spleen, which indicated an acute infection process. Typical pyogranulomas with central necrosis and peripheral mononeuclear cells were observed in kidney clearly. These results illustrate the dual role of granulomatous lesions in chronic bacterial infections.